Hybrid molecule SA-10 and its PLGA nanosuspension protect human and rodent retinal ganglion cells against neuronal injury - Jennifer H. Pham; Wei Zhang; Kim-Tuyen T. Le; Bindu Kodati; Charles E. Amankwa; Biddut DebNath; Gretchen A. Johnson; Thien T. Bui; Rachel Y. Gitter; Jonah P. Gutierrez; Brendon R. Hatfield; Rojan Satyal; et al. (BMC Neuroscience)
Abstract Background Glaucoma is a leading cause of blindness characterized by retinal ganglion cell (RGC) degeneration. SA-10, a dual-acting compound with ROS scavenging and NO-donating properties, was evaluated to enhance RGC survival and function in models of oxidative stress, ischemia/reperfusion (I/R) injury, and neurotrophic factor (NF) deprivation. Methods SA-10-loaded nanoparticles (SA-10-NP) with a size of 279.6 ± 20.9 nm, polydispersity index of 0.34, and encapsulation efficiency of 80.6% were synthesized and tested for sustained release over 28 days. I/R injury was induced by elevating intraocular pressure to 120 mmHg for 60 min in C57BL/6J mice, followed by SA-10-NP treatment (1% w/v). Retinal ganglion cell function and survival were evaluated using PERG and PVEP. Oxidative stress in primary RGCs and retinal explants was induced using endothelin-3 (ET-3), and the effects of SA-10 (10 µM) on ROS levels were assessed. In ex vivo human retinal explants (HREs), SA-10 treatment effects on oxidative stress markers NRF2 and HMOX1 were analyzed. Results SA-10-NP improved PERG amplitudes (112.96% in females, p < 0.01) and PVEP amplitudes (67.53% in females, p < 0.01), preserving RGC density in both central and mid-peripheral regions. Immunohistochemistry showed upregulation of Hmox1 and downregulation of TNF-α in the SA-10-NP-treated group. SA-10 significantly reduced ROS levels in primary RGCs and retinal explants exposed to endothelin-3 (ET-3), decreasing fluorescence intensity by 25.9% (p < 0.01) and 14.7% (p < 0.0001), respectively. SA-10 upregulated oxidative stress markers (NRF2 and HMOX1) and enhanced RGC survival in NF-deprived HREs. Conclusions SA-10 demonstrated significant ROS reduction and preserved RGC survival and function in both I/R mouse models and HREs, with immunohistochemistry confirming upregulation of Hmox1 and downregulation of TNF-α in the SA-10-NP-treated group. SA-10-NP provided sustained drug delivery and bioavailability, showcasing strong neuroprotective effects and offering a potential therapeutic strategy for glaucomatous optic neuropathy and other neurodegenerative conditions.